2012
DOI: 10.1007/s13197-012-0885-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of colour and texture changes of beef during storage

Abstract: The influence of the packaging films, aerobic and vacuum conditions, and refrigeration storage temperature (0, 4 and 10°C) on colour and texture of raw meat were studied during a 2-week storage period in order to analyze kinetics of colour and texture changes. The rate of redness decrease was most noticeable at the highest storage temperature and aerobic conditions and these changes were well described by the firstorder reaction. Texture parameter reflected a progressive softening during storage for both films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
2
26
2
Order By: Relevance
“…For striploin muscle, there was no noticeable correlation between the brightness and the consumers' evaluations of the beef. Even though it has been claimed that the color of meat is most dependent on a* parameter (Dlivera et al, 2013;Sen et al, 2014), in our experiment a strong negative correlation was observed between the a* and b* values and the consumer color evaluations (r > 0.7 at significance level of 0.05). This suggests that yellowness is as important as redness in the consumer assessment.…”
Section: Relationship Between the Instrumental Parameters And Consumecontrasting
confidence: 71%
See 1 more Smart Citation
“…For striploin muscle, there was no noticeable correlation between the brightness and the consumers' evaluations of the beef. Even though it has been claimed that the color of meat is most dependent on a* parameter (Dlivera et al, 2013;Sen et al, 2014), in our experiment a strong negative correlation was observed between the a* and b* values and the consumer color evaluations (r > 0.7 at significance level of 0.05). This suggests that yellowness is as important as redness in the consumer assessment.…”
Section: Relationship Between the Instrumental Parameters And Consumecontrasting
confidence: 71%
“…The color most desired by consumers is associated with freshness and is light red for beef (Mistura & Colli, 2009;Zakrys-Waliwander et al, 2011;Dlivera et al, 2013). Therefore, in addition to preserving freshness and quality, the packaging should also provide for the stability of the meat color Mancini et al, 2009;Troy & Kerry, 2010;Kameník et al, 2014;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the b * values showed a subtle decrease (P < 0.05) from 10.96 (day 0) to 9.91 (day 15). It has been reported that redness (a * value) is the most crucial parameter about the fresh beef color, compared with L * and b * values (Olivera et al, 2013). In our study, the surface a * values of beef presented an apparent decline tendency with the extended storage, especially on day 15, a * value dropped to 5.58, which was extremely undesirable for consumers.…”
Section: Characteristics Of Meat Colormentioning
confidence: 47%
“…It has been extensively used in some related studies on meat tenderness in past several years (Jensen et al, 2009;Olivera, et al, 2013). In order to increase the significance of the previous results, GO analysis and protein-protein interaction were employed to trace the potential predictors responsible for meat color traits.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…Koohmaraie () also believed that aging could lower the hardness of the meat during postmortem storage. In addition previous studies also reported a decline in WBSF of packaged beef steaks during storage (Grobbel et al, ; Olivera et al, ; Vitale et al, ). In this study, the types of packaging did not affect the change in WBSF values.…”
Section: Resultsmentioning
confidence: 79%